The Kefaya Movement A Case Study of a Grassroots Reform Initiative - Oweidat, Nadia (RAND Corporation, 2008)
Kefaya was an indigenous movement for political reform organized in late2004 in opposition to the regime of Egyptian President Hosni Mubarak. Thisexamination of Kefaya's birth, accomplishments, and decline is based on ananalysis of the work of Egyptian scholars and Arabic-language media reports(including online and new media), as well as structured interviews withpersons associated with and observers of Kefaya and the Muslim Brotherhood.